Project approach to modernization of infocommunication processes for workers of network pharmaceutical companies - A. A. Hussein (Новые технологии, 2019)
General trend for informatization and digitalization, which is manifested in all areas of economic and social activity, is most clearly manifested in the aspect of employee communications with consumers of their products and services in socially significant organizations, including network pharmaceutical companies. At the same time, the personnel management objects of such companies include both direct interactions with customers and processes of intranet communications, from the position of the client-oriented approach adopted in this article.The aim of the research is to substantiate the potential of the project approach for an objective assessment of the quality of infocommunications of employees of multidisciplinary pharmacy chains and to develop proposals for their improvement based on the idea of doublecircuit (external and internal circuits) of their labor interactions. Using the information model of managing a regional pharmaceutical company developed by the author, the priority of managerial influences on the communication processes of employees and a list of methods and technologies supporting personnel decisions have been determined.